P4_4 Teleportation - Roberts, Declan; Nelms, James; Starkey, David; Thomas, Suzanne (Physics Special Topics, 2012)
Teleportation of human beings is often featured in science fiction as being a marvel of transportation, instantaneously moving people large distances. This paper investigates the time and energy requirements for the data transfers required to teleport a human being. It is concluded that the data needed to fully map a human brain is so high that the time taken for a 0.5GHz bandwidth is 4.85x1015 years, making teleportation impractical.